Chiral Spin-Transfer Torque Induced by Curvature Gradient - Allende-Prieto, S; Castro-Barrera, M (Royal Society of Chemistry, 2024)
This work analyzes the propagation of a transverse domain wall (DW) under the action of an electric current along a nanowire with a curvature gradient. Our results evidence that the curvature gradient induces a chiral spin-transfer torque (CSTT) whose effect on the DW dynamics depends on the direction along which the DW points, evidencing a curvature-induced non-reciprocity in the current-driven DW motion. The origin of the CSTT is explained in terms of a position-dependent effective field associated with the DW profile and the electric current direction. This current-driven chiral effect is responsible for direction-dependent reinforcing or blocking the DW propagation. The emergence of curvature-induced chiral spin transport is a phenomenon to consider when designing spintronic devices. © 2024 The Royal Society of Chemistry.